2022
DOI: 10.1039/d2fo02251f
|View full text |Cite
|
Sign up to set email alerts
|

An agar–polyvinyl alcohol hydrogel loaded with tannic acid with efficient hemostatic and antibacterial capacity for wound dressing

Abstract: Rapid hemostasis, antibacterial effect and promotion of wound healing are the most important functions that wound dressings need to have. In this work, we designed and prepared a hydrogel with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The improvement of the mechanical properties of the XG-based composite hydrogels is also due to the presence of intermolecular hydrogen bonding between the functional groups of XG, PVA, and resveratrol, which reinforced the whole cryogel network. Similar results have also been reported for agar/PVA hydrogels loaded with tannic acid [ 54 ].…”
Section: Resultssupporting
confidence: 90%
“…The improvement of the mechanical properties of the XG-based composite hydrogels is also due to the presence of intermolecular hydrogen bonding between the functional groups of XG, PVA, and resveratrol, which reinforced the whole cryogel network. Similar results have also been reported for agar/PVA hydrogels loaded with tannic acid [ 54 ].…”
Section: Resultssupporting
confidence: 90%
“…In previous research, NYS has shown broad‐spectrum fungicidal activity and effectiveness against some fungal infections resistant to Amphotericin B, making it a desirable compound in topical patches [40] . NYS release in addition to TA would greatly benefit in wound healing which is why TA was not washed from the hydrogel [41–44] …”
Section: Resultsmentioning
confidence: 99%
“…[40] NYS release in addition to TA would greatly benefit in wound healing which is why TA was not washed from the hydrogel. [41][42][43][44]…”
Section: Nystatin Release Kineticsmentioning
confidence: 99%
“…Using the method of counting live cells, it was shown that the biomaterial containing two compounds with antibacterial activity—chitosan and tannic acid—caused complete inhibition of the growth of Gram-negative E. coli bacteria. Cheng et al [ 128 ] also incorporated tannic acid as an antibacterial agent into a PVA and agar-based hydrogel. In vitro tests proved that the biomaterial with the lowest tested concentration of TA (1%) revealed high antibacterial activity against S. aureus and E. coli .…”
Section: Antimicrobial Biomaterialsmentioning
confidence: 99%